Do Inferior Tribunals have the Power to declare a Law Unconstitutional? A case in support - Borgers, Ingmar (Revue générale de droit, 1988)
This paper discusses the ability of an inferior tribunal to declare invalid a law it has the duty to apply as being contrary to the Canadian Charter of Rights and Freedoms or the Quebec Charter of Human Rights and Freedoms. It deals with the implications created by these important legislative changes and their effect upon the powers of an inferior tribunal. A brief discussion upon the power prior to these amendments is undertaken to better place the issue in its current context.